Implementasi Pembelajaran Berdiferensiasi pada Materi Pantun Berbantuan Media Komik Betawi - Aprilia Pratami, Cindy; Soviana Devi, Wika (CV. Multi Kreasi Media, 2024)
This research is related to the implementation of differentiated learning on pantun material assisted with Betawi comic media. The importance role of the teachers in implementing the innovations is crucial to maintain the relevance of curriculum development. The characteristics of different learners are also very important to learn. The impact of this neglect is the lack of effective understanding of students in the learning process. Educators are required to be able to design new learning technologies and methodologies. In addition to new methods, the learning media created is also an attraction for students. The combination of differentiated learning and illustrated comic media is expected to create imaginative, creative and innovative graduates. Differentiated learning is an educational approach that aims to accommodate the various learning needs of learners. Through this learning, educators can adjust methods, materials and assessments to suit the diverse abiliti es, interests and learning styles of learners. Effective media to implement learning can increase students' interest and motivation to learn, as well as facilitate understanding of the material. The research method used is classroom action research with the subject of Junior High School students. The purpose of this study is to explore the effectiveness of differentiated learning using comic media as well as finding obstacles in its application at Almanar Azhari Junior High School class VII. The results of this study show that differentiated learning on pantun material assisted with Betawi comic media is effective in recognizing the learning style of each student. In order to achieve learning objectives and improve the achievement of each student.